FVIII inhibitor surveillance in children with hemophilia A in Indonesia: a report from the Indonesian Pediatric Hematology-Oncology Working Group - Chozie, Novie Amelia; Gatot, Djajadiman; Sudarmanto, Bambang; Susanah, Susi; Purnamasari, Rini; xWidjajanto, Pudjo Hagung Widjajanto; Nugroho, Susanto; Rasiyanti, Olga; Puspitasari, Dian; Riza, Muhammad; Larasati, Maria Christina Shanty; Adiyanti, Sri Suryo; et al. (Korean Society of Hematology, 2022)
Background Factor VIII (FVIII) inhibitor diagnosis and surveillance in Indonesia are challenging owing to geographic conditions and the lack of laboratory facilities nationwide for inhibitor assays. This study aimed to determine the prevalence of FVIII inhibitors in children diagnosed with hemophilia A (HA) in Indonesia. Methods A cross-sectional study was conducted in 12 hospitals in eight provinces of Indonesia between 2020 and 2021. Factor VIII inhibitor screening was performed in a central hemostasis laboratory for all children with HA (≤18 yr) who had received a minimum of 10 exposure days to clotting factor concentrates. The FVIII inhibitor titer was determined using the Bethesda assay. Results Children (388) were enrolled in this study, including 219 (56.4%), 131 (33.8%), and 38 (9.4%) with severe, moderate, and mild HA, respectively. The prevalence of children who developed FVIII inhibitors was 37 out of 388 (9.6%). Factor VIII inhibitors were found in 25/219 (11.4%) severe, 11/131 (8.3%) moderate, and 1/38 (2.6%) children with mild HA. Thirteen children had low-titer inhibitors and 24 had high-titer inhibitors, with a median of 9.44 (1.48‒412.0) Bethesda Units. Among 13 children with low-titer inhibitors, eight underwent a confirmation test, of which five tested negative and were classified as transient. A significant difference in annual joint bleeding rate was found between patients with low and high inhibitor titers and those without inhibitors (P＜0.001). Conclusion Factor VIII inhibitor prevalence in Indonesia was relatively low. However, the risk factors that may contribute to FVIII inhibitor development among Indonesian patients require further study.